Bender Typed Piezoelectric Multilayer Actuator - Byung-GukAhn; Dong-KyunLee; Deuk-YoungHan; Chong-YoonKang; Ji-WonChoi; Hyun-JaiKim; Seok-JinYoon (한국세라믹학회, 2003)
A bender typed multilayer actuator (BMA) for decreasing the depolarization effect was designed and fabricated. Unlike bimorph and multimorph actuators in which depolarization occurred, the BMA did not generate depolarization because the polarization and the electric field directions are the same. The simulated results indicate that higher displacement of the BMA can be achieved by increasing input voltage. Compared with the multimorph actuator, the proposed actuator is expected to extend a life time as well as acceptable voltage range.